Evaluation of Abdominal Fetal Electrocardiography in Early Intrauterine Growth Restriction - Velayo, Clarissa L.; Funamoto, Kiyoe; Silao, Joyceline Noemi I.; Kimura, Yoshitaka; Nicolaides, Kypros (Frontiers in Physiology, 2017)
OBJECTIVES. This descriptive study was performed to evaluate the capability of a non-invasive transabdominal electrocardiographic system to extract clear fetal electrocardiographic (FECG) measurements from intrauterine growth restricted (IUGR) fetuses and to assess whether abdominal FECG parameters can be developed as markers for evaluating the fetal cardiac status in IUGR. METHODS. Transabdominal FECG was attempted in 20 controls and 15 IUGR singleton pregnancies at 20+0-33+6 weeks gestation. Standard ECG parameters were compared between the study groups and evaluated for their correlation. Accuracy for the prediction of IUGR in cut off values of the different fetal electrocardiographic parameters was also determined. RESULTS. Clear P-QRST complexes were recognized in all cases. In the IUGR fetuses, the QT and QTc intervals were significantly prolonged (p = 0.017 and p = 0.002, respectively). There was no correlation between ECG parameters and Doppler or other indices to predict IUGR. The generation of cut off values for detecting IUGR showed increasing sensitivities but decreasing specificities with the prolongation of ECG parameters. CONCLUSION. The study of electrocardiophysiology is now feasible through a non-invasive transabdominal route. This study confirms the potential of FECG as a potential clinical screening tool to aid diagnosis and management of fetuses after key limitations are addressed. In the case of IUGR, both QT and QTc intervals were significantly prolonged and thus validate earlier study findings where both these parameters are found to be markers of diastolic dysfunction. This research is a useful prelude to a test of accuracy and Receiver Operating Characteristics (ROC) study.